"I got it FIRST": Antecedents of competitive consumption of a new product. (July 2023) - Park, Jihye; Li, Wenhan
Abstract: When a new product of a well-known brand is released, consumers wait in line as early as possible to increase their chances of purchasing the product. This research investigated the two-stage competitive arousal model of a new product purchase competition. Results of a structural equation modeling with a multi-group analysis approach showed that competitive arousal was a central psychological state stimulated by product uniqueness, scarcity, popularity, need for uniqueness, and self-enhancement value, influencing the intention to queue in line. Practical insights in targeting the right consumers and promoting a new product to draw optimal attention from consumers were further discussed. Highlights: Competitive consumption of a new product has been prevalent among consumers. The two-stage competitive arousal model was unique for the new product's competitive purchase condition. Competitive arousal is facilitated by product factors and consumer traits in the first stage. Competitive arousal leads individuals to take competitive actions in the second stage.